EVALUATION OF CORROSION RESISTANCE OF STEEL SHEETS FOR AUTOMOTIVE INDUSTRY WITH THE USE OF THE SPOTFACE TECHNIQUE - Alberto Nei Carvalho Costa; José Carlos dos Santos; José Eduardo Ribeiro de Carvalho; Neilor da Silva Oliveira; Thiago de Souza Martins (Tecnologia em Metalurgia, Materiais e Mineração, 2013)
Innovation, leading to weight and cost reduction, is a key word concerning the design of steel auto body for auto makers that aim to keep and improve their market share worldwide. On the other hand, auto body life, which is related to the corrosion resistance of the materials employed, should always be considered. The latter has led the auto makers to team up with suppliers to find the best solutions concerning the materials selection. The end result always points towards different sets of steels either zinc-coated or zinc alloyed-coated. Taking all these aspects into consideration, the overall challenge the auto makers face is to mitigate the time required for selection and narrow down the options available. This paper studies the corrosion resistance of several materials applied on steel auto bodies using the technique named spotface, which main advantage is reducing the time required by the traditional scribe to evaluate and compare different materials, when they are submitted either to accelerated or field corrosion testing. Concerning the accelerated corrosion testing, they were performed according to the General Motors do Brasil’s requirements.